Manufacture of yarns and textiles from novel resorbable phosphate-based glasses - Wang, Yunqi (2018)
Phosphate-based glass fibre reinforced poly-lactic acid (PGF/PLA) composites containing biocompatible and fully biodegradable constituents can provide huge clinical benefits in comparison with bio-inert metallic materials, such that they have a great potential for use of bone fracture fixation devices. The previous lab-scale phosphate glass fibre production can only provide single filament, which limited the use of these fibres as they could only be produced as non-woven preforms such as unidirectional or random fibre mats. The work conducted in this project explored the manufacture of continuous multifilament phosphate glass fibre strands and textiles products with a pilot plant in co-operation with Sinoma Ltd. in Nanjing, China. The aim of the work conducted in this thesis was to scale-up the manufacture of continuous multifilament PGF strands and textile products. Additionally, this work explored the design and manufacturing of novel PGF/PLA commingled yarns, and also highlighted the successful feasibility and proof-of-concept for producing textiles and textile composites for use as bone plates for load bearing applications. Novel zinc-containing glass formulations based on the system P2O5-CaO-MgO-Na2O-ZnO were investigated in terms of thermal, structural, degradation, viscosity and fibre tensile properties, and also the feasibilities for industrial-scale multifilament fibre production. The replacement of monovalent Na+ with the higher field strength Zn2+ increased the glass transition, crystallization, melting, liquidus temperatures, softening temperature, density and viscosity. The initial addition of ZnO in the glass system increased the mechanical properties of fibres and the chemical durability of the glasses investigated. However, once the addition of a particular amount of ZnO was exceeded, the mechanical properties of fibres and chemical durability of the glasses were seen to decrease. These glass compositions may not be suitable for industrial-scale fibre production. Therefore, the glass code P48B12Na1 was used in following research for the production of multifilament yarns, textiles and commingled textiles. The industrial-scale multifilament production of phosphate glass fibre (PGF) strands was achieved successfully. The textile yarns were produced by combining fibre strands using the ring-spinning method. The PGF textiles were prepared using a home-made inkle loom. PGF textile composites were prepared using film stacking method. The crimp of yarns was found to have a significantly negative effect on the flexural properties of the textile composites in comparison with unidirectional (UD) composites. The number-average molecular weight of PLA was also found to reduce after the production of PLA films and PLA plates, in comparison with the original PLA pellets used. The pilot scale production of PGF/PLA commingled yarns and textiles with designed fibre volume fraction was achieved successfully. Commingled textiles showed a great benefit in improving the mechanical properties of textile composites as compared to the ones produced using film stacking method. The effects of compression moulding parameters (factors) on flexural strength and consolidation quality of PGF/PLA commingled textile based composites were investigated using statistical experimental range analysis, including processing temperature, preheating time, compression time and pressure. Processing temperature provided the greatest effect on the flexural strength of all the composites, followed by preheating time. The statistical experimental design methodology was confirmed to be a powerful tool to study and optimise the processing parameters for production of PGF/PLA commingled textile based composites. Unidirectional (UD) composites, textile composites and 0°/90° composites based on PGF/PLA commingled yarns were prepared by compression moulding. Effects of edge sealing, fibre content and orientation on the degradation performance of the composites were investigated during immersion in phosphate buffered saline (PBS) solution at 37 °C for 28 days. With an increase in fibre content, the initial flexural strength was improved, and all were comparable to human cortical bone. The sharp decrease in flexural properties was seen for all composites during the initial 3 days of immersion was attributed to the loss of fibre/matrix interfacial adhesion. The edge sealed composites revealed less decrease in both pH and weight loss in comparison with unsealed composites due to the fast diffusion of water into the PLA matrix. No significant improvement on the retention of mechanical properties for edge sealed composites was found. Additionally, composites with higher fibre volume fraction revealed faster degradation of PGFs and lower retention of mechanical properties over immersion period of 28 days. It was suggested that 0°/90° composites was more superior than textile composites due to the 0°/90° composites with the desired biaxial mechanical properties were much easier to be designed and manufactured of due to their higher flexibility in layout of commingled UD fabric preforms.